Penguatan Pemasaran Digital Dan Variasi Produk Bagi Pemilik Usaha “Healthy Food” - Sri Budi Cantika Yuli; Arifin, Zainal; Bambang Widagdo (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Purpose  – This community service activity aims to provide solutions to the problems of the Service Partner, namely the Housewives Group of Healthy Food business owners on Jalan Kenanga Indah, Lowokwaru District, Malang City, which is chaired by Mrs. Sunayah. There are two partner problems; 1) Do not yet have digital marketing media through social media because they still use direct sales promotion and 2) Not yet innovating for Healthy Food product variations Design/methodology/approach – The activity method used is training and mentoring for Service Partners, including consumer identification, target market, market share and business owner capacity; designing social media marketing strategies; creating profiles; updating digital marketing profiles; making Healthy Food variations as well as evaluating and monitoring activities Findings – The results of this service activity include first; training and assistance in creating an Instagram account @_healthyfood_malang with a number of follower accounts (Followers) of 2,711 and the PKM Team continues to train Service Partners to document training activities, the results of making Healthy Fruit and Healthy Vegetables, designing photos and writing using templates, uploading to Instagram accounts and assisting Service Partners to be able to increase Followers. The PKM team also trained Service Partners to follow as many Instagram accounts as possible to find new customers and expand the market. The results of the second activity; The PKM team trained the Service Partners to make variations of Healthy Food, namely Healthy Fruit and Healthy Vegetables. Monitoring and evaluation activities for success are carried out by the PKM Team in accordance with each systematic that has been previously trained Originality/value – The implication of this service activity is that the capacity of the Service Partners has increased, knowledge about social media marketing strategies through Instagram and how to develop product marketing has increased. The general public has alternative healthy foods that can be consumed and ordered online through Instagram social media. At the same time, the Service Partner can develop a variety of Healthy Food. The novelty of this service activity is that it is carried out by a group of housewives to improve skills and help supplement the family economy